PEMBERHENTIAN KEPALA DAERAH KARENA MELAKUKAN TINDAK PIDANA KORUPSI MENURUT UNDANG-UNDANG HUKUM ISLAM - Wery Gusmansyah (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2018)
Abstract: The process of dismissal according to the Act is without going through the proposal of the DPRD and being tried directly by the Corruption Court. When the file has been submitted to the court a temporary stop will be applied. After obtaining a permanent decision (inkracht), if proven to be innocent then no later than 30 days the Regional Head concerned will be reactivated. If proven guilty the President dismisses the Governor and / or Deputy Governor and the Minister dismissing the Regent and / or Deputy Regent and Mayor and / or Deputy Mayor. The case of corruption that is authorized to prosecute in Islamic law is the Mazhalim Court to decide on the case (verdict / verdict). Then the Amir was given 10 days after the ruling was issued to defend the charges. If the plea is rejected, then he is immediately dismissed if at least two-thirds of the members of Majelis al-Shura are present at the special session to carry out the dismissal. Furthermore, the authority to dismiss the Regional Head is the Caliph. In general, the mechanism of dismissal of Regional Heads has many differences but there are several aspects of equality such as the President / Caliph who has the authority to dismiss the Regional Head.Keywords: Dismissal, Regional Head, Corruption Crime, Islamic Law.